The impact of hexagonal boron nitride encapsulation on the structural and vibrational properties of few layer black phosphorus. (28th February 2019) - Birowska, Magdalena; Urban, Joanna; Baranowski, Michał; Maude, Duncan K; Plochocka, Paulina; Szwacki, Nevill Gonzalez
Abstract: The encapsulation of two-dimensional layered materials such as black phosphorus is of paramount importance for their stability in air. However, the encapsulation poses several questions, namely, how it affects, via the weak van der Waals forces, the properties of the black phosphorus and whether these properties can be tuned on demand. Prompted by these questions, we have investigated the impact of hexagonal boron nitride encapsulation on the structural and vibrational properties of few layer black phosphorus, using a first-principles method in the framework of density functional theory. We demonstrate that the encapsulation with hexagonal boron nitride imposes biaxial strain on the black phosphorus material, flattening its puckered structure, by decreasing the thickness of the layers via the increase of the puckered angle and the intra-layer P–P bonds. This work exemplifies the evolution of structural parameters in layered materials after the encapsulation process. We find that after encapsulation, phosphorene (single layer black phosphorous) contracts by 1.1% in the armchair direction and stretches by 1.3% in the zigzag direction, whereas few layer black phosphorus mainly expands by up to 3% in the armchair direction. However, these relatively small strains induced by the hexagonal BN, lead to significant changes in the vibrational properties of black phosphorus, with the redshifts of up to 10 cm −1 of the high frequency optical mode A g 1 . In general, structural changes induced by the encapsulation process open the door to substrate controlled strain engineering in two-dimensional crystals.